STRATEGI PENINGKATAN KUALITAS KERJA PEGAWAI DALAM RANGKA PERBAIKAN KINERJA PADA DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK DAN PEMBERDAYAAN MASYARAKAT KOTA LUBUKLINGGAU - Mery Nopryanti; Dheo Rimbano; Abdullah Hehamahua (Jurnal Interprof, 2018)
The departement of woman growthing and children protection, and citizen growthing in Lubuklinggau City, and the first information who received means that the competation of worker in there must be increased, the special for their job description, the worker haven’t had the experience who sitcble with their position. According to the quality of result work have been maximal tyhe of the work durring this time. The purpose of this research are 1). to know the quality result work ini thw Departement of Women growthing and children protection, and 2). tho know the strelegly to incluade repair the result of working in the Departement of Woman Growthing and Children Protection and citizen growthing in Lubuklinggau city. The collecting sample used interview and observation method. The analysis sample use the descriptive method. The result of this reserrch are 1). the quality of the work in the departement of womwn growthing and childrenprotection and citizen are still good, it can be show the approch of their result work, 2). The strategy of inereving to repaired the result work inwomwn growthing children protection and citizen growthinng in Lubuklinggau City increaived the factulity and skill worker by fullewed trainning and enchment to incluade ther compection.